สถานภาพและบทบาทสตรีใต้ในวรรณกรรมหนังตะลุง ของหนังกั้น ทองหล่อ: Status and Role of Southern Women in Nang Talung Literature of Nang Khan Thonglor - ชูเย็น, ภควันต์; คุ่มเคี่ยม, อลิสา; จีนนุ่น, พัชลินจ์ (Journal of Humanities and Social Sciences (HUSOKKU), 2022)
บทคัดย่อ บทความวิจัยนี้มีวัตถุประสงค์เพื่อวิเคราะห์สถานภาพและบทบาทสตรีใต้ในวรรณกรรมหนังตะลุงของหนังกั้น ทองหล่อ ศิลปินแห่งชาติ ด้านบทบาทและสถานภาพของสตรีใต้ และด้านมโนทัศน์ของชาวใต้ที่มีต่อบทบาทและสถานภาพต่อสตรีใต้ ผลการศึกษาพบว่า หนังกั้นนำเสนอสถานภาพและบทบาทของสตรีใต้ใน 5 ลักษณะ ได้แก่ นักรบ ผู้ปกครอง ลูก ภรรยา มารดา โดยวรรณกรรมหนังตะลุงของหนังกั้นแสดงให้เห็นมโนทัศน์ของชาวใต้ทีมีต่อสตรีใต้ผ่านสถานภาพและบทบาทใน 2 ลักษณะ ลักษณะแรกคือมโนทัศน์ด้านคตินิยมของชาวใต้ที่มุ่งเน้นให้สตรีใต้มีการศึกษา รู้จักครองเรือน และประพฤติตนเหมาะสม ลักษณะที่สองคือมโนทัศน์ด้านความเสมอภาคทางเพศที่เน้นให้สตรีใต้มีสถานภาพและบทบาทเท่าเทียมกับผู้ชาย ทำให้เห็นความคิดของนายหนังที่มีทั้งความทันสมัย ตระหนักคุณค่า และความสำคัญของสตรีใต้ที่สอดรับกับบริบทท้องถิ่นอย่างชัดเจน คำสำคัญ: สถานภาพและบทบาท สตรีใต้ วรรณกรรมหนังตะลุง Abstract The objectives of this research article were to analyze the status and roles of Southern women in the Nang Talung literature of Nang Khan Thonglor, the national artist, and to analyze the women from the worldview of Southerners. The results of the study revealed that Nang Kan presents the status and roles of Southern women in five characteristics: status and role of warriors, guardians, children, wives, and mothers. Nang-Talung literature of Nang Kan illustrates Southerners' worldview toward Southern women through their status and role in two aspects. First, the southern ideological worldview emphasizes women in the South should be educated, be a householder, and behave appropriately. Second, the worldview of gender equality aspect emphasizes that Southern women have the same equal status and roles as men. Furthermore, this reveals the ideas of Mr. Nang that are modern and appreciates the importance of women in the south that are clearly in line with the local context. Keywords: status and role, southern women, shadow play literature